Analisis Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (Studi Kasus Pada Badan Pengelola Pendapatan Daerah Kabupaten Sintang Tahun 2010-2017) - Wulan Purnama Sari; Miftahuljannah Miftahuljannah (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2019)
The purpose of this research is to know the influence of local tax and the region retribution on the locally generated revenue. The sample is laporan realisasi BAPPEDA in Sintang region in 2010-2017. This research used statistical test tool  20.0. Double linier regresi analysis technic, classical asumsion test, test F and test T, coefficient of determination for independent variable test to dependent variabel. Significan level that used in this research is 0,05. From this research, coefficient of determination R2 is 80,2%. Locally generated revenue  variable can be explained by local tax (X1) and local retribution (X2). F count value  (15,165) > F tabel (5,79) So Ha can be accepted. Partially, there is no influence between local tax to locally generated revenue. The hypothesis test shown that local tax give the positive influence and there is no significan. Based on the result of this research , the hypothesis test shown that local retribution has negative influence and there is no significan to locally generated revenue.